Aging-associated fermentation of palm oil-mill effluent enhances its organo-fertilizer value and the desired agronomic effects in low-fertility soils - Daniel Onyedikachi Ugwu; Parker Elijah Joshua; Sunday Ewele Obalum; Ndeari King Dedan; Obi Uzoma Njoku (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: Fresh palm oil-mill effluent (POME) is toxic and when added to agricultural soils often inhibits plant growth. In this study, the prospects of temporal fermentation of POME with aging in enhancing its organo-fertilizer value before application to low-fertility soils were evaluated.